Association of loneliness and social isolation with all-cause mortality among older Mexican adults in the Mexican health and aging study: a retrospective observational study - Ashuin Kammar-García; Ricardo Ramírez-Aldana; Paloma Roa-Rojas; Luis Raymundo Lozano-Juárez; Sergio Sánchez-García; Pamela Tella-Vega; Carmen García-Peña (BMC Geriatrics, 2023)
Abstract Background Plenty of evidence shows how social isolation and loneliness are associated with increased risk for numerous diseases and mortality. But findings about their interactive or combined effects on health outcomes and mortality remains inconclusive. Objective Analyze the longitudinal association of loneliness, social isolation and their interactions, with the all-cause mortality among older adults in Mexico. Methods A retrospective observational study was conducted. Mexican adults older than 50 years were included. Data from the Mexican Health and Aging Study (MHAS) in the 2015 and 2018 waves were used. The subjects were classified according to their level of loneliness and the presence of social isolation. Multivariate logistic regression analyzes were performed to determine the degree of association between loneliness and social isolation with all-cause mortality at a 3-year follow-up. Results From the total sample of 11,713 adults aged 50 years or over, 707 (6%) did not survive, 42% presented loneliness, and 53% were classified as socially isolated. After multivariate adjustment only social isolation (OR = 1.30, 95%CI:1.03–1.64) was associated with all-cause mortality, loneliness (Mild: OR = 0.83, 95%CI:0.59–1.16; Severe: OR = 1.03, 95%CI:0.71–1.64), and the interaction between loneliness and social isolation were not associated with all-cause mortality. Conclusion Social isolation, but not loneliness or their interaction, was associated with all-cause mortality in Mexican adults older than 50 years. This finding may help direct possible future interventions that help improve mental health in older adults from a highly collectivistic country.